Direct Synthesis of Renewable Dodecanol and Dodecane with Methyl Isobutyl Ketone over Dual‐Bed Catalyst Systems. Issue 5 (18th January 2017) - Sheng, Xueru; Li, Ning; Li, Guangyi; Wang, Wentao; Wang, Aiqin; Cong, Yu; Wang, Xiaodong; Zhang, Tao
Abstract: For the first time, we demonstrated two integrated processes for the direct synthesis of dodecanol or 2, 4, 8‐trimethylnonane (a jet fuel range C12 ‐branched alkane) using methyl isobutyl ketone (MIBK) that can be derived from lignocellulose. The reactions were carried out in dual‐bed continuous flow reactors. In the first bed, MIBK was selectively converted to a mixture of C12 alcohol and ketone. Over the Pd‐modified magnesium– aluminium hydrotalcite (Pd‐MgAl‐HT) catalyst, a high total carbon yield (73.0 %) of C12 oxygenates can be achieved under mild conditions. In the second bed, the C12 oxygenates generated in the first bed were hydrogenated to dodecanol over a Ru/C catalyst or hydrodeoxygenated to 2, 4, 8‐trimethylnonane over a Cu/SiO2 catalyst. The as‐obtained dodecanol can be used as feedstock in the production of sodium dodecylsulfate (SDS) and sodium dodecyl benzene sulfonate (SDBS), which are widely used as surfactants or detergents. The asobtained 2, 4, 8‐trimethylnonane can be blended into conventional jet fuel without hydroisomerization. Abstract : Dual‐bed catalysis : For the first time, dodecanol and jet fuel range C12 ‐branched alkane (2, 4, 8‐trimethylnonane) are directly synthesized with high carbon yield (∼70 %) by using dual‐bed catalyst systems with hydrogen and methyl isobutyl ketone (MIBK) that can be derived from lignocellulose.